(untitled) (World Economics and Finance Bulletin, 2026)
The reliability of financial statements largely depends on the correct recognition, valuation and audit of real estate objects, which constitute the main part of corporate assets. This article analyzes the current state of real estate audit practice in Uzbekistan and studies the main factors affecting its effectiveness. The study examined the methodological, institutional and technological aspects of real estate audit. In particular, the differences between market and balance sheet values, the insufficiency of cadastral data, and the problems of integration between valuation and audit processes were identified. Based on the results of the analysis, scientific and practical proposals were developed to improve real estate audit. These include the introduction of specific audit standards, the development of a digital cadastre system, and strengthening cooperation between auditors and appraisers